Growth and Stress Axis Responses to Dietary Cholesterol in Nile Tilapia (Oreochromis niloticus) in Brackish Water - Xu, Chang; Li, Erchao; Xu, Zhixin; Su, Yujie; Lu, Minghui; Qin, Jian G.; Chen, Liqiao; Wang, Xiaodan (Frontiers in Physiology, 2018)
Six isonitrogenous and isocaloric diets were formulated to contain 0% (control), 0.4%, 0.8%, 1.2%, 1.6% or 2.4% dietary cholesterol and fed to juvenile Nile tilapia (Oreochromis niloticus) (2.20 ± 0.12 g) twice daily to apparent satiation for 8 weeks in triplicate at a salinity of 16. Fish fed 0.4% cholesterol showed a higher weight gain and specific growth rate and a lower feed coefficient ratio than fish fed other diets. No difference was found in the survival of Nile tilapia fed various levels of cholesterol. Cholesterol in the serum and liver and low-density lipoprotein cholesterol in the serum increased with the increase in the dietary cholesterol content. Relative to the control, no significant difference was found in the expression of head kidney P450scc mRNA between treatment groups. The expression of head kidney 11β-HSD2 mRNA was the highest in the control group, and it decreased significantly with increasing levels of diet cholesterol. Fish fed 0.4% or 1.2% cholesterol had a higher 20β-HSD2 mRNA expression in the head kidney than those fed other diets. Fish fed 0.8% cholesterol had higher expressions of GR1 and GR2B mRNA in the liver than other groups. Fish fed 0.4% cholesterol had the highest activity of gill Na+/K+-ATPase. Fish fed 0.8% to 2.4% cholesterol had higher serum cortisol contents than the fish in the control group and the fish fed 0.4% cholesterol. This study suggests that dietary cholesterol is not essential for Nile tilapia survival in brackish water, but 0.4% cholesterol supplementation in the Nile tilapia diet contributes to the improvement of hyperosmotic adaptation and increases in gill Na+/K+-ATPase activity and serum cortisol content by regulating the hypothalamic-pituitary-interrenal stress axis.